2022
DOI: 10.3390/agronomy12030601
|View full text |Cite
|
Sign up to set email alerts
|

Mainstreaming Urban Agriculture: Opportunities and Barriers to Upscaling City Farming

Abstract: Urban Agriculture (UA), i.e., the production of crops or rearing of livestock in cities, is growing in popularity. Upscaled UA is increasingly gaining support from policy makers, funders, local authorities and other key actors across the globe. Radical forms of the concept, in the form of edible rooftops, urban farms and high-tech growing projects, are becoming more commonplace in our cityscapes; enabling production on a level not witnessed previously. With the mainstreaming of large-scale UA comes the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It has been observed that the participation of community members in UA may be impeded by a dearth of knowledge or inclination towards the subject matter [51]. Furthermore, it is plausible that community constituents may exhibit reluctance towards engaging in UA as a result of time limitations or competing obligations [50,52]. The existence of community-based organizations that interact with community members and offer instruction and preparation on UA can serve to enhance involvement and enhance the efficacy of UA in the region.…”
Section: Nutrition Adequacymentioning
confidence: 99%
“…It has been observed that the participation of community members in UA may be impeded by a dearth of knowledge or inclination towards the subject matter [51]. Furthermore, it is plausible that community constituents may exhibit reluctance towards engaging in UA as a result of time limitations or competing obligations [50,52]. The existence of community-based organizations that interact with community members and offer instruction and preparation on UA can serve to enhance involvement and enhance the efficacy of UA in the region.…”
Section: Nutrition Adequacymentioning
confidence: 99%
“…Despite the controversy, the persistence of small-scale agroecological production systems worldwide demonstrates their continued importance for community livelihoods, cultural identity, and the environment. The presence of small farms also indicates the resilience of solidarity-based food production movements, which are frequently undermined by government subsidies for monocrop production and corporate consolidation [ 4 , [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the increasing consumption rate and yard potential, urban farming is a solution-driven by the Magelang Government to achieve food security. Urban farming is the cultivation, processing, and distribution of food and other products through plant cultivation and livestock raising to meet local food needs [5]. Over the past 20 years, urban farming has contributed to minimizing the impact of climate change and improving the quality of people's lives in urban areas [6].…”
Section: Introductionmentioning
confidence: 99%